The best of marketing Rx : for entrepreneurs, marketing practitioners, and marketing students - Roberto, Ned. (Manila, Philippines : Rex Book Store, 2015)
This edition of The best of marketing Rx includes selected columns on the marketing mix and this mix's marketing levers in their individual functions, as well as in pairs and triads.
Chapter 1. Market segmenting for business-growing -- Chapter 2. Brand Positioning as consumer behavior -- Chapter 3. Innovations in product and process -- Chapter 4. Market Responsive pricing -- Chapter 5. Marketing's Marketer Side: The total Marketing mix -- Chapter 6. Marketing's Marketer Side: The Marketing Mix Levers.
Keywords: MARKETING